Sustainable Urban Transport Management in Luang Prabang, the World Heritage City in Lao PDR - CHITTAPHONE, Bounpheng; Yangsansay, Chahue (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims to: (1) examine stakeholders’ perceptions regarding the strengths, weaknesses, opportunities, and threats (SWOT) of the transport system in Luang Prabang, and (2) explore approaches for developing sustainable urban transport management in Luang Prabang. This research employs a qualitative approach, using interviews as the primary data collection tool. The sample group consists of 10 participants drawn from the Department of Public Works and Transport, the Tourism Department, the Urban Planning and Administration Office, traffic police, urban planning experts, transport consultants, and other relevant stakeholders. Data were analyzed using a thematic analysis approach, focusing on identifying, analyzing, and organizing patterns or themes. The research findings reveal that: 1) he SWOT analysis of the transportation system in Luang Prabang indicates key strengths such as a compact urban layout, strong heritage awareness, and its role as a tourist city with less dependence on vehicles. Weaknesses include limited public transport, insufficient parking, weak traffic law enforcement, and road infrastructure constraints. Opportunities involve integrating tourism with transport, adopting new technologies, international support, a shift to electric vehicles, and public participation. Threats include increasing vehicle numbers, tourism-related risks, conflicts between conservation and development, and environmental impacts. 2) Sustainable urban transport development in Luang Prabang should focus on improving the system, addressing congestion and pollution, and meeting demand. It requires better management, policy planning, and coordination among agencies, along with greater awareness of sustainability. As a UNESCO World Heritage city, development must balance transport improvements with heritage conservation. Future efforts should emphasize comprehensive, modern, and environmentally friendly management rather than only expanding roads or increasing vehicles.